Tn and sialyl‐Tn antigens, aberrant O‐glycomics as human disease markers. Issue 9 (9th September 2013) - Ju, Tongzhong; Wang, Yingchun; Aryal, Rajindra P.; Lehoux, Sylvain D.; Ding, Xiaokun; Kudelka, Matthew R.; Cutler, Christopher; Zeng, Junwei; Wang, Jianmei; Sun, Xiaodong; Heimburg‐Molinaro, Jamie; Smith, David F.; et al.
<x xml:space="preserve">Abstract</x> In many different human disorders, the cellular glycome is altered. An interesting but poorly understood alteration occurs in the mucin‐type O‐glycome, in which there is aberrant expression of the truncated O‐glycans Tn (GalNAcα1‐Ser/Thr) and its sialylated version sialyl‐Tn (STn) (Neu5Acα2, 6GalNAcα1‐Ser/Thr). Both Tn and STn are tumor‐associated carbohydrate antigens and tumor biomarkers, since they are not expressed normally and appear early in tumorigenesis. Moreover, their expression is strongly associated with poor prognosis and tumor metastasis. The Tn and STn antigens are also expressed in other human diseases and disorders, such as Tn syndrome and IgA nephropathy. The major pathological mechanism for expression of the Tn and STn antigens is compromised T‐synthase activity, resulting from alteration of the X‐linked gene that encodes for Cosmc, a molecular chaperone specifically required for the correct folding of T‐synthase to form active enzyme. This review will summarize our current understanding of the Tn and STn antigens in terms of their biochemistry and role in pathology.